Acoso escolar y su afectación en las relaciones sociales de un joven de 14 años del cantón Baba - Macias Pinela, Amada Antonela (2023)
Bullying is a topic that has been presented for some time, managing to go unnoticed because society considered it as something normal to occur in educational institutions to create bonds of friendship and build character, however, this leads to living with problems in mental health that were caused and treated on time. It is for this reason that this case study is aimed at dealing with bullying and its incidence in the social relations of a 14-year-old boy. Which allowed me to reach a diagnosis, through the use of different techniques such as clinical observation, semi-structured interview and use tools such as the observation guide and clinical history, among others. In conclusion, it was possible to analyze the incidence of bullying in the patient's social relationship, allowing a presumptive diagnosis based on the DSM-5 and ICD-10 criteria; social anxiety disorder (social phobia) 300.23, for which a therapeutic plan with a cognitive behavioral approach is recommended, within which different types of techniques were used to reduce symptoms and modify thoughts.